A novel in situ test for the design of drilled foundations. Issue 1 (2nd January 2016) - Bradshaw, A. S.; Reyes, B.; DeVillers, C.; Sauco, P.
Abstract : This paper describes a novel in situ test concept called the Borehole Plug Test that could improve the design of drilled foundations. The test method involves casting a small-scale grout plug at the bottom of a typical borehole for site investigations and load testing the plug to obtain the load transfer behaviour and the maximum unit side shear resistance (or bond strength). The plug test results can then be used to simulate full-scale load tests for design purposes. A field trial is presented that demonstrated its feasibility and potential benefits. Additional research is needed both to study fundamental behaviour and to collect more field data to compare with full-scale static load test data in a variety of soil and rock types.